A community-based study on diabetes medication nonadherence and its risk factors in rural Tamil Nadu - Murugan Venkatesan; Amol R Dongre; Kalaiselvan Ganapathy (Wolters Kluwer Medknow Publications, 2018)
Context: Medication nonadherence is common among diabetics and it is one of the leading public health challenges. Aims: The aims of this study were to find the prevalence of nonadherence to diabetic medication and to identify various factors associated with it. Settings and Design: This study was conducted in 34 villages of the field practicing areas of rural health training center. This was a mixed method study design. Subjects and Methods: It was conducted among 328 type 2 diabetic patients. The quantitative data were collected from diabetic patients and qualitative data from health-care providers to identify their perceived barriers for patient's nonadherence. Statistical Analysis Used: Collected data were entered in Epi Info (3.5.3) and analyzed using SPSS version 24 software. Results: The prevalence of low adherence to diabetic medication was 45.4% among the study population. Bivariate analysis shows significant association with the patients who are literate (odds ratio [OR] = 0.6, confidence interval [CI] = 0.38-0.95), hypertensive (OR = 1.6, CI = 1.04-2.5), taking treatment from private facility (OR = 0.54, CI = 0.34-0.87), perceived lack of satisfaction with doctor-patient relationship (OR = 3.3, CI = 1.3-8.3), and perceived lack of knowledge about diabetes (OR = 2.03, CI = 1.29-3.1) with low adherence to medication. Conclusions: The prevalence of nonadherence to medications is common among diabetics in rural areas, and there is a need to strengthen the primary health-care system in addressing barriers to achieve better health outcomes.